Validity of self-reported weight: a study of urban brazilian adults - Maria I. Schmidt; Bruce B. Duncan; Mário Tavares; Carísi A. Polanczyk; Lúcia Pellanda; Paulo M. Zimmer
In order to evaluate the validity of self-reported weight for use in obesity prevalence surveys, self-reported weight was compared to measured weight for 659 adults living in the Porto Alegre county, RS Brazil in 1986-87, both weights being obtained by a technician in the individual's home on the same visit. The mean difference between self-reported and measured weight was small (-0.06 +/- 3.16 kg; mean +/- standard deviation), and the correlation between reported and measured weight was high (r=0.97). Sixty-two percent of participants reported their weight with an error of < 2 kg, 87% with an error of < 4 kg, and 95% with an error of < 6 kg. Underweight individuals overestimated their weight, while obese individuals underestimated theirs (p<0.05). Men tended to overestimate their weight and women underestimate theirs, this difference between sexes being statistically significant (p=0.04). The overall prevalence of underweight (body mass index < 20) by reported weight was 11%, by measured weight 13%; the overall prevalence of obesity (body mass index > 30) by reported weight was 10%, by measured weight 11%. Thus, the validity of reported weight is acceptable for surveys of the prevalence of ponderosity in similar settings.